2005
DOI: 10.1091/mbc.e04-09-0803
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitylation of a Melanosomal Protein by HECT-E3 Ligases Serves as Sorting Signal for Lysosomal Degradation

Abstract: The production of pigment by melanocytic cells of the skin involves a series of enzymatic reactions that take place in specialized organelles called melanosomes. Melan-A/MART-1 is a melanocytic transmembrane protein with no enzymatic activity that accumulates in vesicles at the trans side of the Golgi and in melanosomes. We show here that, in melanoma cells, Melan-A associates with two homologous to E6-AP C-terminus (HECT)-E3 ubiquitin ligases, NEDD4 and Itch, and is ubiquitylated. Both NEDD4 and Itch particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 33 publications
9
60
0
Order By: Relevance
“…1C). The six other responding patients (LAU 618, LAU 42, LAU 321, LAU 672, LAU 4, and LAU 814) showed responses against three additional regions of Melan-A: Melan-A 1-20 , Melan-A [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] , and Melan-A [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] . These results showed that among 16 melanoma patients tested, Ͼ50% of them displayed Melan-A-specific CD4 T cell responses.…”
Section: Melanoma Patients Display Melan-a-specific Cd4 T Cell Responsesmentioning
confidence: 99%
See 4 more Smart Citations
“…1C). The six other responding patients (LAU 618, LAU 42, LAU 321, LAU 672, LAU 4, and LAU 814) showed responses against three additional regions of Melan-A: Melan-A 1-20 , Melan-A [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] , and Melan-A [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] . These results showed that among 16 melanoma patients tested, Ͼ50% of them displayed Melan-A-specific CD4 T cell responses.…”
Section: Melanoma Patients Display Melan-a-specific Cd4 T Cell Responsesmentioning
confidence: 99%
“…We then focused on the responses to the region Melan-A [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] , because this region contains the immunodominant HLA-A2-restricted epitope Melan-A 26 -35 and defining Th epitopes in the same region is of practical interest. We derived clones using the IFN-␥ capture assay and flow cytometry-assisted cell sorting to select CD4 T cells from the primary cultures that were able to respond to short-term stimulation with Melan-A [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] .…”
Section: Cd4 T Cell Responses To the Melan-a 21-40 Peptide Are Hla-drmentioning
confidence: 99%
See 3 more Smart Citations